Mixed convection flow about a solid sphere embedded in a porous medium filled with a nanofluid - Leony Tham,; Roslinda Nazar, (Universiti Kebangsaan Malaysia, 2012)
A steady laminar mixed convection boundary layer flow about an isothermal solid sphere embedded in a porous medium filled with a nanofluid has been studied for both cases of assisting and opposing flows. The transformed boundary layer equations were solved numerically using an implicit finite-difference scheme. Three different types of nanoparticles, namely Cu, Al2O3 and TiO2 in water-based fluid were considered. Numerical solutions were obtained for the skin friction coefficient, the velocity and temperature profiles. The features of the flow and heat transfer characteristics for various values of the nanoparticle volume fraction and the mixed convection parameters were analyzed and discussed.